The phenomenon of toxic masculinity on violence in a romantic relationship status - Umaroh, Ayu Khoirotul; Dewi, Aldise Zulianing (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2025)
Intimate partner violence, particularly when fueled by toxic masculinity, remains a significant issue in Indonesia, where patriarchal social norms dominate societal structures. Toxic masculinity, characterized by traits such as dominance, control, and emotional repression, serves as the foundation for violence in intimate relationships, often justified as an expression of love and care. This study aims to explore the impact of toxic masculinity on relationship violence from the perspective of victims. A qualitative phenomenological approach was employed to understand the subjective experiences of five female informants, aged 20-21, who have experienced various forms of violence—verbal, emotional, psychological, and physical—within their romantic relationships. The findings indicate that toxic masculinity is expressed through behaviors such as possessiveness, jealousy, verbal abuse, physical violence, and emotional manipulation. These behaviors are often driven by power imbalances within relationships, shaped by deeply entrenched gender norms. Hegemonic masculinity, which reinforces male dominance over women, was identified as a key factor in justifying such violence. The study emphasizes the critical need for education that challenges toxic masculinity norms and promotes gender equality to reduce the prevalence of relationship violence. The findings provide valuable insights for policy development and intervention strategies, offering recommendations for addressing gender-based violence in Indonesia and promoting a more equitable society.